Synthesis and biological studies of new heterocyclic compounds containing pyrazole, thiazole and/or thiadiazole moieties - Eman Kamal Mousa Dewidar; Sobhy Mohamed Gomaa (Cairo : Eman Kamal Mousa Dewidar, 2016)
The original work of the submitted thesis consists of two research projects: In the first part: A new series of 7-arylazopyrazolo[5,1-c][1,2,4] triazoles was synthesized via reaction of 3-amino-4-(arylhydrazono)-4,5-dihydropyrazol-5-one with hydrazonoyl halides using triethylamine as a basic catalyst. The structure of all the synthesized compounds was confirmed on the basis of elemental and spectral analyses data. Moreover, the antimicrobial and antitumor activities of these compounds were evaluated and the results obtained indicate the weak efficacy of some of them as antibacterial agents. But, the results of antitumor activity against HepG-2 liver cancer and HCT-116 colon cancer of some derivatives showed good activity in comparison with the reference drugs. In the second part: A novel series of 5-arylazothiazoles was prepared from 2-(-1-morpholino-1-(2-arylhydrazono)propan-2-ylidene)-hydrazinecarbothioamide by different methods. The structures of the newly synthesized compounds were established on the basis of spectroscopic evidences and their synthesis by alternative methods. Moreover, the newly synthesized products were evaluated for their anti-cancer activities and the results show that some derivatives have good to mild utility as antitumor operators. Moreover, the computational studies using MOE 2014.09 software are confirming the results of biological activity
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Organic Chemistry
Issued also as CD
Keywords: New heterocyclic compounds containing pyrazole; Thiadiazole moieties; Thiazole